The Effects of Financial Education : Evidence from Finnish Lower Secondary Schools - Kalmi, Panu (Wiley, 2017)
We study the effects of a peer-to-peer learning environment designed for lower secondary schools that provides financial education using games, videos and other materials provided online. We exploit a quasi-experimental setting with a control group to evaluate the effects of the learning environment and to distinguish them from the effects of a general economics course. We use two different samples from subsequent years to check the robustness of the results. Our results demonstrate the positive effects of financial education on financial knowledge, but no significant effects are shown in terms of savings behaviour. Further, although we find that girls improve their scores much more than boys after the educational intervention, we also find that this results from general education rather than from the specific intervention. Finally, we find that increased knowledge and enhanced savings behaviour are strongly correlated, supporting the notion that financial education holds promise for changing financial behaviour.
Keywords: fi=Taloustiede|en=Economics|